Low‐dose acyclovir prophylaxis for the prevention of herpes simplex virus disease after allogeneic hematopoietic stem cell transplantation. Issue 5 (29th July 2013) - Kawamura, K.; Wada, H.; Yamasaki, R.; Ishihara, Y.; Sakamoto, K.; Ashizawa, M.; Sato, M.; Machishima, T.; Terasako, K.; Kimura, S.‐I.; Kikuchi, M.; Nakasone, H.; et al.
Abstract: Background: Currently, acyclovir (ACV) at 1000 mg/day is widely used as prophylaxis in the early phase of hematopoietic stem cell transplant (HSCT) in Japan. However, low‐dose ACV (200 mg/day) has been shown to prevent varicella zoster virus reactivation in the middle and late phases of HSCT. Methods: Therefore, in this study, we decreased the dose of ACV to 200 mg/day in the early phase after HSCT. We analyzed 93 consecutive herpes simplex virus (HSV)‐seropositive patients who underwent allogeneic HSCT for the first time in our center between June 2007 and December 2011. Results: Before August 2009, 38 patients received oral ACV at 1000 mg/day (ACV1000) until day 35 after HSCT, whereas 55 patients received oral ACV at 200 mg/day (ACV200) after September 2009. We compared the cumulative incidence of HSV infection in the 2 groups. Oral ACV was changed to intravenous administration because of intolerance in 66% and 45% of the patients in the ACV1000 and ACV200 groups, respectively ( P  = 0.060). The probability of severe stomatitis (Bearman grade II–III) was 76% and 60% in the ACV1000 and ACV200 groups, respectively ( P  = 0.12). The number of patients who developed HSV disease before day 100 after HSCT was 0 in the ACV1000 group and 2 in the ACV200 group, with a cumulative incidence of 3.6% ( P  = 0.43). HSV disease in the latter 2 patients was limited to the lips and tongue and was successfully treated with ACV or valacyclovir at a treatment dose. Conclusion: ACV at 200 mg/day appeared to be effective for preventing HSV disease in the early phase after HSCT.